(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
The church is dedicated to the Celtic saint Maelrubha. Of Irish royal lineage, he is said to have been born in AD 642, and to have ultimately reached Applecross about 673 by way of Iona. His Ross-shire churches may therefore have been founded at the end of the seventh century, or at the beginning of the eighth. He is said to have died in 722. The few documentary references to the church are presented along with an architectural account. An elaborate floriated cross survives in the churchyard. A second stone has a fine large wheel-cross head carving. The sacrament house was rediscovered in 1908 and probably dates from the 15th century.